Effect of a pleural checklist on patient safety in the ultrasound era. Issue 3 (21st March 2013) - See, Kay Choong; Jamil, Khalizah; Chua, Ai Ping; Phua, Jason; Khoo, Kay Leong; Lim, Tow Keang
<x xml:space="preserve">Abstract</x> Little information exists on patient safety improvement methods in the era of thoracic ultrasonography. We evaluated the effect of a checklist in a before‐and‐after study of 255 patients. Complications decreased from 8.3% to 1.5%, suggesting that a pleural checklist may further enhance safety of ultrasound‐guided procedures.